2015
DOI: 10.1080/00103624.2014.997388
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Forms of Copper and their Association with Soil Properties and Uptake in Major Soil Orders in Semi-arid Soils of Punjab, India

Abstract: all soils were considered, total Cu content ranged from 7 to 37 mg kg −1 , while DTPA-extractable and soil solution plus exchangeable Cu contents ranged from 0.30 to 3.26 mg kg −1 and from 0.02 to 0.43 mg kg −1 , respectively. Copper adsorbed onto inorganic sites ranged from 0.62 to 2.6 mg kg −1 and that onto oxide surfaces ranged from 2.0 to 13.2 mg kg −1 . The Cu bound by organic sites ranged from 1.2 to 12.2 mg kg −1 . The magnitudes of different forms of Cu in soils did not exhibit any consistent pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The positive correlation were observed with organic carbon and clay content. The results of Sharma et al, [26] and Meena et al, [27] showed identical results with the results of the current study. The high negative influence of pH towards available copper might be due to be adsorption, fixation and precipitation.…”
Section: Dtpa-cusupporting
confidence: 91%
“…The positive correlation were observed with organic carbon and clay content. The results of Sharma et al, [26] and Meena et al, [27] showed identical results with the results of the current study. The high negative influence of pH towards available copper might be due to be adsorption, fixation and precipitation.…”
Section: Dtpa-cusupporting
confidence: 91%
“…The higher content of Cu in Entisol and Inceptisol is ascribed to variation in exogenic carbon inputs that stimulated the biomass and activity of microbes, thereby increasing the decomposition rate and release of micronutrients in soils [47,56,60]. The higher content of Cu in Inceptisols might be associated with an increase in clay content, resulting in its adsorption or fixation [1]. Similar results showing the higher content of DTPA-Cu in Inceptisols were reported by some workers [1].…”
Section: Dtpa-extractable Copper (Cu)mentioning
confidence: 52%
“…The greater EC under Aridisol may be due to its higher evaporation, leading to the deposition of soluble salts [32]. The higher EC under Aridisols might primarily be also due to greater accumulation of salts in soils [1].…”
Section: Soil Ecmentioning
confidence: 99%
See 2 more Smart Citations